STUDENTS’ ANALYSIS ON CONVERSATIONAL IMPLICATURES OF CIAYUMAJAKUNING DRAMA SCRIPTS - Jaufillaili, Jaufillaili; Mahmud, Mahmud (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2019)
Pragmatics is added into the new curriculum of English Education Department. Pragmatics deals with hidden meaning (Wray et al, 1998). Grice?s theory of Cooperative Principle and Maxims are a common study in Pragmatics. To relate the study of Pragmatics and other subject in English Education Department, the writers asked students to analyze the drama scripts they had performed. The analysis is about conversational implicatures in Ciayumajakuning drama scripts which involved Grice?s theory of Cooperative Principle and Maxims. It is a qualitative study that applies a case study. The writers took students? analysis on four drama scripts of Ciayumajakuning as the data source. The aims of this research are: 1) to describe how students analyze the flouting of maxims in the drama script, and 2) to describe how students analyze conversational implicatures in the drama script. The research finding shows that 1) students analyzed the flouting of maxims based on Grice?s theory of maxims. They are maxim of quantity, maxim of quality, maxim of relation and maxim of manner. 2) Students analyzed conversational implicatures in two ways, the first is through the relationship between the question and the answer of the target conversant. The second, some students provided some possible implicatures that might be derived by readers. Then, the students chose one implicature as the most appropriate one for some reasons